THE INFLUENCE OF FOREIGN AND DOMESTIC INVESTORS ON THE PRICE AND VOLUME OF STOCKS THE INDONESIAN STOCK EXCHANGE: TESTING JANUARY EFFECT - Sri Hermuningsih; Pristin Prima Sari; Anisya Dewi Rahmawati (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2023)
This research aims to test and find empirical theoretical evidence regarding the influence of January on changes in stock prices and volume by foreign and domestic investors. The research method uses a quantitative method. The researcher uses sample data on the LQ-45 company's stock return report on January 2, 2020 to 2023 from Indonesia Stock Exchange by using Multiple Regression Analysis with IBM SPSS 20. This research has found that partially foreign and domestic investor have significant impact on volume of stock while Domestic investor have significant impact on price stock but Foreign Investor does not significant impact on price stock. Simultaneously Foreign and domestic investor have significant impact on price and volume of stock.  The contribution and benefit of this research is to expand the scientific and theoretical models of the January effect based on trading prices and share volume by foreign and domestic investors